Latin American Popular Art in a Museum: How Things Become Art - Sanfuentes, Olaya (Artium Quaestiones, 2019)
In 1943 when Universidad de Chile celebrated its centennial all Latin American nations were invited to participate in the commemorative events. One of the most interesting was the Exhibition of American Popular Art at the Museo Nacional de Bellas Artes(National Museum of Fine Arts) which brought together the objects from participating countries. The Universidad de Chile´s invitation asked countries to send functional objects that were part of the people´s daily lives. The exhibition was very successful, critically acclaimed, and highly attended. But above all, it planted the seed for what was to become the Museo de Artes Populares Americanas(American Popular Art Museum) functioning to this day. In this essay I would like to highlight a series of contexts, actors and institutions behind the phenomena: specific incarnations of Pan Americanism during the Second World War; the Latin American perspective in general and in particular, the Chilean perspective of the university´s role in society; the new value of Latin American arts since the 20thcentury. These contexts and events are useful to shed light on the “social life” of the objects that were part of the exhibition and they also help us to understand a dynamic definition of art which emerged from the recognition of craft in use as worthy of exhibition in a National Fine Arts Museum and then to remain at the permanent collection of a popular art museum. The radical importance of this essay is that it constitutes an example of a thing which represents not just art but also other values. In a midst of the World War II, Latin American Popular Art represented peace. The objects of the exhibition were seen as incarnations of Latin American cultural identity and historiography has gone on to view Latin American culture as a specific contribution to peace effort.